Utilización de aceite comestible reutilizado y borra de café en la obtención de una vela llena aromática - Ramírez Gonzaga, Michael Alexander (2024)
The objective of this research was to evaluate the effect of using reused edible oil and coffee grounds in obtaining a full aromatic candle. A 23 factorial arrangement was designed with 9 treatments and three replications each. Factor A was proposed with three percentages of reused edible oil (20%, 25%, and 30%) and factor B with three percentages of coffee grounds (2%, 4%, and 6%). The physicochemical results of the reused edible oil showed values outside the acceptable limits for edible vegetable oils in terms of acidity value (2.35 mg KOH/g), humidity (0.15%), and viscosity (57.5 m.P.a.s), although the peroxide value remained within the established parameters (5.99 Meq.O 2 /Kg). The coffee grounds presented levels of humidity (9.75%) and ash (2.56%) consistent with the specialized literature. It was found that level a1 (20%) was favorable to avoid secondary ignition of the candles, while levels a3 (30%) and b1 (2%) provided a longer ignition time (1136.44 min and 1112.11 min respectively). The sensory test revealed that treatments T2 (a1b2) and T1 (a1b1) were the most acceptable for the color attribute, while, for aroma, there were no differences (Sig. ≥ 0.05). The results suggest that the use of reused edible oil and coffee grounds can be a viable option for the production of scented candles, as long as the percentages are adjusted to avoid secondary ignition problems and maximize the useful life of the candles.